Mobile heart rate monitoring and advising system / Mohd Faizal Kamaruddin - Kamaruddin, Mohd Faizal (2015)
Heart rate is also known as pulse, the number of times a person heart beats per minute. A normal rate depends on the individual, age, body size, heart conditions, whether the person is sitting or moving, medication use and even air temperature. As a human the first thing that we need to make sure our heart performance in a good condition is we need to do a daily exercise. Those people who always do the exercises, the heart performance become well. The problem is people do not have a monitor and do not know how to measure heart rate manually. Even though in a Play Store have an application to measure heart rate but the application do not give any idea or advice to the user on what people need to do after have the heart rate result. For this project mobile heart rate monitoring and advising system the developer will use Extreme Programming Methodology while in documenting and developing this project. This methodology will be the guideline to make sure this project succeed. This application provides a benefit to the user in measuring heart rate and gives advice to them. It can be effective way to the people to get an advice from the applications since peoples hard to seek to the expert to be advice. The scope of this project is only focusing on Android mobile user. In future it will be available for IOS user.